Peningkatan Kualitas Belajar Matematika Melalui Strategi Pembelajaran Inkuiri Pada Siswa Kelas VIIIA SMP Negeri 1 Kotabaru - Rahmi Yuliana (STKIP Paris Barantai, 2019)
The research located in Junior High School 1 Kotabaru. This type of research is Classroom Action Research which consists of several planning, implementation, observation and reflection. This study aims to improve the quality of mathematics learning in class VIII A of SMP Negeri 1 Kotabaru by using inquiry learning strategies that are applied in mathematics learning. The place for conducting this research in Junior High School 1 Kotabaru. The subject of this study was all students of class VIIIA Junior High School 1 Kotabaru. The technique of obtaining data in this study is 1) Data on improving student achievement is taken by member tests for students. 2) Data about teaching and learning learning or learning processes when taking actions taken using a collection of observations. The type of data obtained is quantitative data obtained from the results of learning tests and qualitative data obtained from observations on the implementation of learning. The data analysis technique in this study is the results of the study analyzed using descriptive analysis and the results of observations analyzed qualitatively. The results of the first cycle showed that 28 students in 7 students (25.00%) were in the very low category, 6 students (21.43%) were in the low category, 2 students (7.14%) ) in the medium category, 8 students (28.57%) were in the high category, and 5 students (17.86%) were in the very high category. The results of the study in the second cycle obtained data that of 28 students were 10 students (35.71%) in the very high category, 12 students (42.86%) were in the high category, 2 students (7.14%) )) are in the moderate category, 4 students (14.29%) are in the low category and no students are in the very low category. The results of the analysis of the average cognitive learning outcomes of class VIII students of SMP Negeri 1 Kotabaru taught with Inquiry Learning Strategies on the discussion of the Circle can be categorized as high. Based on the Criteria for Teaching Completion (KKM) can compare students taught with inquiry learning strategies have improved the quality of learning. This discusses the results of student learning after the evaluation is moved from cycle I to cycle II. Obtained from the average value of students in cycle I Significant increase in cycle II. In addition, the learning process is selected using an observation sheet that shows a high increase in students' abilities. Classical completeness has also been successful in cycle II. Keywords: Quality of Learning Mathematics, Inquiry Learning Strategy